PENGARUH PENAMBAHAN SULFUR PADA PROSES PENCAIRAN BATUBARA BANKO - Herman Hidayat; Adiarso Adiarso (Jurnal Energi dan Lingkungan (Enerlink), 2006)
The effect of adding sulfur in Central Banko coal liquefaction is examined usingautoclave reactor with limonite catalyst from Soroako, at 450oC, H2 initialpressure = 9 Mpa, holding time = 60 minutes, and S/Fe ratio varies from 1, 2, 3dan 6. It is found that there is significant increase in distillates yield by 53,81% forthe increase of S/Fe ratio from 1 to 2, and at the same time CLB decreases from53,5% to 29,47%. This is because the amount of pyrrhotite for S/Fe ratio =2 ishigh and enough to promote cracking to convert coal to distillates or oil. For S/Feratio = 3, the increase of distillates or oil yield is not significant, so does for S/Fe= 6. This concludes that adding more sulfur in Central Banko coal liquefactionusing limonite catalyst from Soroako is not effective and therefore does notinfluence much to the oil yield. This is because the particle size and amount ofpyrrhotite already achieves equilibrium for S/Fe ratio = 2. The changing of S/Feratio does not give much effect to the yields of H2O, CO+CO2, C1~C4,andhydrogen consumption as well..Kata Kunci : limonit Soroako, rasio S/Fe,yield distilat, yield CLB, pirhotit, yieldH2O, yield CO+CO2, yield C1~C4, konsumsi gas hidrogen